Efektifitas Pengaruh Penggunaan Metode Pembelajaran Discovery dan Asesmen Essay Untuk Meningkatkan Prestasi Belajar dan Pemahaman Metakognisi Biologi Siswa SMA di Kota Bekasi - Fauzan, Ahmad (BIO-EDU: Jurnal Pendidikan Biologi, 2021)
The purpose of this research is to find out the effectiveness of the use of discovery learning methods and essay assessment. Research method is quasi experiment and use pretest - posttest control group design. The data obtained were analyzed with descriptive statistics and parametric inferential statistics. Data on understanding metacognition and learning achievement using test instruments of learning results as well as metacognition tests are measured by criteria of metacognition ability. Control class data normality test with Shapiro-wilk 0,108 and 0,123 > 0,005 normal distributed data. Test normality of experiment class data 0,114 and 0,110 > 0,005 normal distributed data. Test the simultaneous similarity of variants with Box'M 0.001 < 0.005 then the dependent variables have the same simultaneous variants. Homogeneity test using Levene's Test 0,845 and 0,311 > 0,005 then homogeneous distributed data. Multivariate homogeneity test using Hotteling's trace manova 0,000 ,0,000 and 0,001 < 0,005 homogeneous data in mltivariate. Testing the main effect hypothesis to one 0,000 and 0,000 < 0,005 there is a significant influence of learning methods on dependent variables, main effect of the second hypothesis of 0,000 and 0,000 < 0,005 there is a significant influence of assessment techniques on dependent variables, interaction effect testing 0,001 and 0,000 < 0,005 there is a significant influence of interaction on dependent variables.